Quantitative assessment of intermolecular interactions by atomic force microscopy imaging using copper oxide tips - Mönig, Harry; Amirjalayer, Saeed; Timmer, Alexander; Hu, Zhixin; Liu, Lacheng; Díaz Arado, Oscar; Cnudde, Marvin; Strassert, Cristian Alejandro; Ji, Wei; Rohlfing, Michael; Fuchs, Harald (Nature nanotechnology, 2018)
Atomic force microscopy is an impressive tool with which to directly resolve the bonding structure of organic compounds 1 – 5 . The methodology usually involves chemical passivation of the probe-tip termination by attaching single molecules or atoms such as CO or Xe (refs 1 , 6 – 9 ). However, these probe particles are only weakly connected to the metallic apex, which results in considerable dynamic deflection. This probe particle deflection leads to pronounced image distortions, systematic overestimation of bond lengths, and in some cases even spurious bond-like contrast features, thus inhibiting reliable data interpretation 8 – 12 . Recently, an alternative approach to tip passivation has been used in which slightly indenting a tip into oxidized copper substrates and subsequent contrast analysis allows for the verification of an oxygen-terminated Cu tip 13 – 15 . Here we show that, due to the covalently bound configuration of the terminal oxygen atom, this copper oxide tip (CuOx tip) has a high structural stability, allowing not only a quantitative determination of individual bond lengths and access to bond order effects, but also reliable intermolecular bond characterization. In particular, by removing the previous limitations of flexible probe particles, we are able to provide conclusive experimental evidence for an unusual intermolecular N–Au–N three-centre bond. Furthermore, we demonstrate that CuOx tips allow the characterization of the strength and configuration of individual hydrogen bonds within a molecular assembly. Using a rigid tip removes artefacts associated with imaging the strongly varying tip–sample potential of intermolecular sites by atomic force microscopy.